Facile preparation of NH2-functionalized black phosphorene for the electrocatalytic hydrogen evolution reaction. Issue 6 (29th January 2018) - Shao, Lianyi; Sun, Hongming; Miao, Licheng; Chen, Xiang; Han, Mo; Sun, Jianchao; Liu, Shuang; Li, Lin; Cheng, Fangyi; Chen, Jun
Abstract : We report a facile solid exfoliation method to prepare NH2 -functionalized few-layer black phosphorene for use as an electrocatalyst for the hydrogen evolution reaction. Abstract : A new facile and green solid exfoliation method using urea-assisted ball milling is reported here to prepare NH2 -functionalized few-layer black phosphorus (BP) nanosheets. The thickness of the obtained nanosheets is about 2.15–4.87 nm. The NH2 -BP nanosheets exhibit enhanced electrocatalytic hydrogen evolution reaction (HER) performance with an overpotential of 290 mV at −10 mA cm −2, a Tafel slope of 63 mV dec −1 and a turnover frequency of 3.21 s −1 at an overpotential of 290 mV, which drastically surpass those of the bulk BP. This electrocatalytic activity of NH2 -BP nanosheets in alkaline electrolyte greatly outperforms that in acidic electrolyte, making it a promising metal-free HER catalyst.